Systemic turbulence and risk spillovers in IBOR rates in Europe - Dziwok, Ewa; Karaś, Marta; Stachura, Michał (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: The aim of the study was to investigate whether all European IBOR rates were similarly susceptible to turbulence as LIBOR rates, and also to analyse systemic risk spillovers between different IBOR rates in Europe and between these rates and the studied banking systems between 2006 and 2022. Methodology: The interbank market turbulence measure (ITM) and ΔCoVaR were applied to analyse immediate spillovers based on coefficient analysis and rank the markets based on turbulence characteristics. Dynamic time warping (DTW) was used to cluster the analysed markets based on the course of turbulence, showing variable and time-changing commonalities in IBOR turbulence. Results: Different levels of overall systemic turbulence for different groups of IBOR rates and in different periods were observed, along with the evidence of dissimilarity and minimal spillovers between LIBOR and IBOR rates after 2011. No evidence was found of risk spillovers from the interbank market towards the banking sector, only the inverse spillovers in the emerging markets were confirmed. Implications and recommendations: The study shows that that there was no systemic-risk related reason for the CEE region to abandon the IBOR rates. The empirical results put the challenges, risks, and feasibility of a full transition toward the new rates in Europe in a new context. The conclusions are relevant for market regulators in the investigated region because they apply not only to the IBOR rates but also to the new rates adopted recently. Originality/value: The paper presents a novel turbulence measure (ITM), developing and employing a set of innovations in calculating ΔCoVaR, as well as the DTW method developed for natural sciences in a financial market setting. Thanks to these methodological innovations the study encompassed an unprecedentedly large sample of countries, including 72 banks that are systemically important for Europe and 19 IBOR term structures, making this paper the most comprehensive analysis of Western, Central, and Eastern Europe with respect to interbank market turbulence.
Argumenta Oeconomica, 2025, Nr 1 (54), s. 225-271
Keywords: IBOR rates; interbank market; systemic turbulence; risk spillovers